Advances in Interdisciplinary Practice in Industrial Design : Proceedings of the AHFE 2019 International Conference on Interdisciplinary Practice in Industrial Design, July 24-28, 2019, Washington D.C., USA /: Proceedings of the AHFE 2019 International Conference on Interdisciplinary Practice in Industrial Design, July 24-28, 2019, Washington D.C., USA. (2020) - Unknown
No abstract available